Struktur dan Komposisi Jenis Tegakan Semai dan Pancang di Hutan Alam Akibat Pemanenan Kayu dengan Teknik Reduced Impact Timber Harvesting - Diana Sofia Hanafiah; Muhdi Muhdi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
The effect of reduced impact timber harvesting technique to structure and species composition of seedling and poles was studied using the data of three plots each sized 100 m x 100 m, which are placed randomly at landing, middle skiddtrail and tips of skiddtrail, respectively. The aim of the study was to know the effect of reduced impact timber harvesting technique to structure and species composition of seedling and poles in tropical forest. The research showed that the forest harvesting caused the changing of the structure and species composition of seedling and poles in natural tropical forest.